2014
DOI: 10.1039/c4ra07973f
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modelling of hybrid composites of nano cenosphere and polycarbonate for a thermal protection system

Abstract: The article explores high temperature applications of novel polycarbonate cenosphere composites for potential use in thermal protection systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The obtained result reveals that the initiation of thermal decomposition and temperature at maximum decomposition was eloquently improved in nano Ph-PC/POSS polymer nanocomposite by the formation of silicon containing heat shield layer a high temperature. In this framework, the suppressed mass loss was imputed by uncovering of the entrapped nano asperities of POSS by the complete mass loss of PC matrix followed by conversion of POSS in silicates after degradation 47 48 49 50 . The suppressed mass loss can also be ascertained by the ordered distribution of POSS in PC lamellae space which yielded shielding effect until the external temperature is high enough to the melting point of the polymer matrix which further concluded by the calculation of latent heat of fusion.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained result reveals that the initiation of thermal decomposition and temperature at maximum decomposition was eloquently improved in nano Ph-PC/POSS polymer nanocomposite by the formation of silicon containing heat shield layer a high temperature. In this framework, the suppressed mass loss was imputed by uncovering of the entrapped nano asperities of POSS by the complete mass loss of PC matrix followed by conversion of POSS in silicates after degradation 47 48 49 50 . The suppressed mass loss can also be ascertained by the ordered distribution of POSS in PC lamellae space which yielded shielding effect until the external temperature is high enough to the melting point of the polymer matrix which further concluded by the calculation of latent heat of fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 6,16 The peak at 2943 cm À1 of pristine PC belongs to the asymmetric stretching vibration, which moves to 2925 cm À1 in the thin lm PC/n-HA composite. 15 The characteristic peak at 1772 cm À1 is due to the carbonyl C]O stretch, and the strongest infrared absorptions in PC are due to the C-O single bond stretches that continue down to 1000 cm À1 , with the strongest of these at 1016 cm À1 .…”
Section: Ir Analysismentioning
confidence: 99%
“…For example, typical fabrication using metals, such as stainless steel (SS), titanium alloy, and cobaltchromium alloys, are expedient for conventional knee and hip implants. 6 A few studies have been reported on the subsequent weakening in mechanical properties of chitosan/HA biocomposites comprising nano-sized HA particles. 1 Nano-hydroxyapatite (n-HA) is a well scrutinized biocompatible inorganic mineral that exemplies intrinsic bone mimicking characteristics for encouraging osteo-development.…”
Section: Introductionmentioning
confidence: 99%
“…30 Restriction of the mobility of the polymer chains by oxide particles present in the FAC also contributes to the improvement which was observed in the thermal stability. 30 Restriction of the mobility of the polymer chains by oxide particles present in the FAC also contributes to the improvement which was observed in the thermal stability.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%